1+2+3+4+5+6+7+8+9-1-2-3-4-5-6-7-8-9*1*2*3*4*5*6*7*8*9:1:2:3:4:5:6:7:8:9=???
Rút gọn biểu thức:
a) 4^5 . 9^4 - 2 . 6^9 / 2^10 . 3^8 + 6^8 .20
b)2 . 8^4 . 27^2 + 4 . 6^9 / 2^7 . 6^7 + 2^7 . 40 .9^4
Thực hiện phép tính:
a, M = \(\sqrt{9+4\sqrt{5}}\) - \(\sqrt{9-4\sqrt{5}}\)
b, N = \(\sqrt{8-2\sqrt{7}}\) - \(\sqrt{8+2\sqrt{7}}\)
Rút gọn
A=\(\sqrt{8+2\sqrt{7}}+\sqrt{8-2\sqrt{7}}\)7
B=\(\sqrt{9+4\sqrt{5}}+\sqrt{9-4\sqrt{5}}\)
1*1*2*2*3*3=0
0*0*1*1*2*2= -100
vay
9*9*8*8*7*7=?
1+2+3+4+5+6+7+8+9+0.1.2.3.4.5.6.7.8.9.0.1-2-3-4-5-6-7-8-9-0=? ai tra loi nhanh va dung cho 1 tick
1+1+1=6
2+2+2=6
3×3÷3=6
√4+√4+√4=6
5+5÷5=6
6×6÷6=6
7 ? 7 ? 7=6
8 ? 8 ? 8 =6
9 ? 9 ? 9=6
10 ? 10 ? 10=6
\(\left(6\right)\dfrac{3\sqrt{x}}{5\sqrt{x}-1}\le-3\)
\(\left(7\right)\dfrac{8\sqrt{x}+8}{6\sqrt{x}+9}>\dfrac{8}{3}\)
\(\left(8\right)\dfrac{\sqrt{x}-2}{2\sqrt{x}-3}< -4\)
\(\left(9\right)\dfrac{4\sqrt{x}+6}{5\sqrt{x}+7}\le-\dfrac{2}{3}\)
\(\left(10\right)\dfrac{6\sqrt{x}-2}{7\sqrt{x}-1}>-6\)
a,\(\sqrt{8+2\sqrt{15}}\) -\(\sqrt{6+2\sqrt{15}}\)
b, \(\sqrt{17-2\sqrt{72}}-\sqrt{19+2\sqrt{18}}\)
c, \(\sqrt{8-2\sqrt{7}}+\sqrt{8+2\sqrt{7}}\)
d, \(\sqrt{12+2\sqrt{11}}-\sqrt{12-2\sqrt{11}}\)
e, \(\sqrt{10-2\sqrt{21}}-\sqrt{9-2\sqrt{14}}\)
tính ;\(\sqrt{2-\sqrt[3]{3+\sqrt[4]{4-\sqrt[5]{5+\sqrt[6]{6-\sqrt[7]{7+\sqrt[8]{8-\sqrt[9]{9}}}}}}}}\)